18F-FDG PET/CT in Graft Versus Host Disease–Associated Polymyositis. (February 2020) - Sood, Apurva; Khadwal, Alka Rani; Lukose, Tinu; Kumar, Rajender; Singh, Harmandeep; Bal, Amanjit; Mittal, Bhagwant Rai
Abstract : Abstract: Graft versus host disease (GVHD) is the most frequent and serious complication of allogenic hematopoietic stem cell transplant. Polymyositis is a rare neuromuscular manifestation of GVHD, which often responds well to corticosteroid and immunosuppression therapy. We present a case of a 38-year-old man with a known case of mixed-phenotype acute leukemia after hematopoietic stem cell transplant presenting with GVHD-associated polymyositis. 18 F-FDG PET/CT done in this case not only helped in the detection of the muscle involvement but also helped in obtaining precise muscle sample for histopathological diagnosis using PET-guided biopsy.